A New Study of the Decorated Cists in Kilmartin Glen, Argyll, Scotland. (1st December 2021) - Watson, Aaron; Bradley, Richard
Abstract : Decorated cists have been identified at three burial cairns in Kilmartin Glen, Mid Argyll. The paper provides a new analysis of the cover slab at Nether Largie North, which features a series of pecked axeheads. Previous studies suggested that they replaced an array of cup marks, but the evidence of photogrammetry suggests a longer sequence and a more complex scheme. The same approach was taken to the decorated cists beneath the Nether Largie Mid cairn and a comparable structure at Ri Cruin. Additional depictions were identified. The carvings within all three cists are organised in similar ways. They date from a period in the Early Bronze Age when metal was imported from Ireland. At the same time, the reuse of older structures suggests a new concern with the past.